Organizational justice and extra-role behavior: examining the relationship in the Malaysian cultural context - Hassan, Arif; Kamariah, Mohd Noor (KENMS-IIUM Press, 2008)
The study examines the role of organizational justice (OJ) in promoting extra role behavior (ERB). OJ is a multi dimensional construct and involves fairness of reward/resource allocation decisions, procedural aspects of these decisions, fairness in interpersonal treatment, and fairness in information and explanation given to employees concerning decisions relevant to them. ERB involves discretionary behavior such as helping other employees and developing ideas, speaking up on issues and voicing concerns relevant to the work group. Recent conceptualizations distinguish ERB from organizational citizenship behavior (OCB), which includes dimensions such as compliance and conscientiousness. The paper is based on a study that uses Van Dyne, Cummings and Parks’ (1995) measure of ERB. This instrument measures two dimensions of ERB, namely, helping (defined as affiliative and promotive behavior) and voice (defined as challenging and promotive behavior). Using data from lower and middle level managers from a mix of organizations, the study validated the four and two dimensional construct of OJ and ERB respectively. Cross cultural studies on social values have identified Malaysia as high on power distance and collectivism. Based on arguments from literature on normative influence of social values on human behavior, the study expected no relationship of OJ with ERB in Malaysia. Results supported the hypotheses.